Vaclav Havel, Simone Weil and Our Desire for Totalitarianism - Fredriksson, Antony (Filosofický ústav AV ČR, 2022)
"Given our troubled history in the 20th century, how is it that nationalism and populism have come to raise their heads again in Europe over the past 20 years? What have we lost? What is it about our liberal, democratic political structures that creates the current atmosphere of mistrust, xenophobia and shortsightedness? How has this development come about, and what is driving it? How should we understand this desire for authoritarianism? In this paper, I will address these questions through a reading of two essays that can be considered to have been written as warning signs regarding a very common tendency within social psychology that entails a development of communities towards authoritarian structures. Simone Weil's essay ""Human Personality"", written in 1943 during her wartime exile in London, and Vaclav Havel's ""The Power of the Powerless"", written in 1978 during his house arrest in Czechoslovakia, both address the potential relapse of Europe into authoritarianism. Neither of these essays should be read as developed theories within political philosophy. They are notes from a dire predicament of crisis, on both a personal and a macro-political level, that investigate the relationship between the subject and society in order to understand the dynamics of totalitarianism. Their strength lies exactly in that they address a present unfolding situation that the authors perceive to have potentially unbearable consequences. This tone of urgency, their way of addressing us from a positionality void of any real power or privilege, and their bold demands for envisioning change beyond given political ideologies, make these essays into unique backdrops for thinking about our current political questions. Both Weil and Havel advocate an open society that permits the subject to cultivate a form of life beyond collective ideology. Both essays address the sensibilities of the subject that do not appeal to identity, common ideology or collectivity in order to thrive. The aim of this paper is to outline this redefinition of the relation between the individual and society in Weil and Havel, as a remedy for our desire for authoritarianism."
Václav Havel, Simone Weil a naše touha po totalitě
Keywords: authoritarianism; belonging; collectivity; moral agency; Simone Weil; autoritářství; sounáležitost; kolektivita; morální jednání; Simone Weil